ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN BOND RATING DI INDONESIA (ANALYSIS INFLUENCE OF FINANCE RATIO TO CHANGE OF BOND RATINGIN INDONESIA) - Maria, Delli (Jurnal Manajemen dan Keuangan, 2008)
Globalization era in this time, openness of information represent matter which is very support growth of corporate world. Various analysis done for the reduce of risk. And financial statement represent one of the correct analysis object to assess efficacy of company and can be made by consideration in course of decision making of invesment. This research aim to study how far finance ratio analysis which contained by financial statement a company have an effect on to change of pertinent Bond Rating company. So that hypothesis to test in this research relate to there is or do not it influence of finance ratio from (indepandent variable) to change Bond Rating ( depandent variable) in Indonesia. Analysis which is used in this research is analyse simple regretion and analysis of doubled regretion. From seven independent variable which weared, result of which is obtained in research show that Timed Interest of Earned Ratio ( TIER), Current Ratio (CuR), Cashflow To Debt Ratio (CFDR), Operating Profit Margin (OPM), and Return On Asset (ROA) by self have an effect on positively signification to change of Bond Rating in Indonesia, at level < 5%. While Debt Ratio (DR) and Debt Equity Ratio (DER), having an effect on negativity of signification to change of Bond Rating. And by simultan monetary ratio which deputized by Timed Interest Earned Ratio (TIER), Current Ratio (CuR), Cashflow To Debt Ratio (CFDR), OpeRating Profit Margin ( OPM), and Return On Asset (ROA), Debt Ratio (DR) and of Debt Equity Ratio to (DER), having an effect on signifikan to change of Bond Rating in Indonesia with contribution 80.8%.Key Word : Bond Rating and Financial Ratio